FINANCIAL RELATIONS IN AGRICULTURE OF THE REPUBLIC OF KAZAKHSTAN - Лухманова, Гульнар; Сеитова, Гульнара; Сартанова, Налима; Абаева, Гулдер (Scientific Journal of Pedagogy and Economics, 2022)
The agro-industrial complex (AIC) is a set of economic sectors related to the production of food and consumer goods from agricultural raw materials and their supply to the population. The current situation in the country required significant financial investments and other economic measures to maintain catastrophically declining agricultural production.Currently, Kazakhstan has noticeably intensified the activity of the state in regulating the agricultural sector of the economy, which is accompanied by the reform of agricultural legislation, primarily in the field of state support for agriculture.Therefore, the main purpose of the study is: to study aspects of financial relations in agriculture. To achieve this goal, it is necessary to solve the following tasks: familiarize yourself with the legislation governing this aspect; consider the system of financial relations in agriculture; formulate the concept of financial support of the state; to study the main types of state financial support for agriculture. The relevance of this work lies in the fact that agriculture is part of the economic system in the state, and in turn commercial structures are included in the financial relations common to the entire economy.